Pengaruh Perendaman Air Hangat Terhadap Kecepatan Perkecambahan Benih Kacang Hijau (Vigna Radiata) - Siska Natalia Zebua (CV. SINAR HOWUHOWU, 2025)
Germination is the initial stage of plant growth and plays a crucial role in determining the success of crop cultivation. One factor influencing germination rate is the pre-treatment of seeds before planting. This study aimed to examine the effect of warm water soaking on the germination rate and percentage of mung bean (Vigna radiata) seeds. The experimental method used four treatments: P0 (no soaking/control), P1 (soaking at 40°C), P2 (50°C), and P3 (60°C), each for 6 hours. The results showed that warm water soaking significantly affected both germination speed and percentage. The P2 treatment (50°C) produced the best results, with the earliest germination (day 1) and the highest germination percentage (95%) by day 7. In contrast, soaking at 60°C resulted in a lower germination rate, likely due to damage to seed tissues. It can be concluded that soaking mung bean seeds in warm water at 50°C for 6 hours is the most effective treatment to enhance germination speed and success.